2022
DOI: 10.1186/s13023-022-02213-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of next-generation sequencing in 87 families with neurodevelopmental disorders

Abstract: Background Neurodevelopmental disorders (NDDs) are a group of heterogeneous conditions, which include mainly intellectual disability, developmental delay (DD) and autism spectrum disorder (ASD), among others. These diseases are highly heterogeneous and both genetic and environmental factors play an important role in many of them. The introduction of next generation sequencing (NGS) has lead to the detection of genetic variants in several genetic diseases. The main aim of this report is to discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Those families who achieved a confirmed genetic diagnosis from the SGP Study after not having achieved one from historic standard testing benefitted from better understanding of prognosis and reproductive risks, giving opportunities for improved reproductive choice in future pregnancy, better ongoing care and, in a small number, the opportunity for a trial of a targeted therapy. Both the overall diagnostic yield and the variation among yield estimates from the 393 families in the SGP Study are broadly in line with those reported for the 100,000 Genomes Project pilot study in NHS England [16], and other studies of genome sequencing in rare inherited conditions [17][18][19]. For those phenotypes with lowest yields (Tumour Syndromes, Renal Syndromes and Cardiovascular lower yields are likely attributable to the standard of care pre-testing comprising comprehensive targeted panels with excellent coverage; alternatively, it may be that these phenotypes are caused by complex genetic abnormalities not captured by the technology and/or identified by the analysis pipeline, such as large structural rearrangement or non-coding variation, polygenic inheritance of genes of modest attributable risk not considered within the clinical analysis pipeline, and/or phenocopies.…”
Section: Discussionsupporting
confidence: 79%
“…Those families who achieved a confirmed genetic diagnosis from the SGP Study after not having achieved one from historic standard testing benefitted from better understanding of prognosis and reproductive risks, giving opportunities for improved reproductive choice in future pregnancy, better ongoing care and, in a small number, the opportunity for a trial of a targeted therapy. Both the overall diagnostic yield and the variation among yield estimates from the 393 families in the SGP Study are broadly in line with those reported for the 100,000 Genomes Project pilot study in NHS England [16], and other studies of genome sequencing in rare inherited conditions [17][18][19]. For those phenotypes with lowest yields (Tumour Syndromes, Renal Syndromes and Cardiovascular lower yields are likely attributable to the standard of care pre-testing comprising comprehensive targeted panels with excellent coverage; alternatively, it may be that these phenotypes are caused by complex genetic abnormalities not captured by the technology and/or identified by the analysis pipeline, such as large structural rearrangement or non-coding variation, polygenic inheritance of genes of modest attributable risk not considered within the clinical analysis pipeline, and/or phenocopies.…”
Section: Discussionsupporting
confidence: 79%
“…Physical examination revealed obvious clinical signs of CdLs, such as long philtrum, long eyelashes, high-arched palate, anteverted nares, and hypospadias. Despite this variant being present in one individual in gnomAD v2 ( (accessed on 15 June 2021)) and in two individuals in gnomAD v3 ( (accessed on 15 June 2021)), and all the in silico predictors tools suggesting it was not deleterious, the absence of additional genetic alterations associated to NDDs and de novo origin reinforced the idea of a probably pathogenic variant [ 11 ]. Hence, when using a general population as a control cohort, the presence of individuals with subclinical disease is always a possibility and thus variants with a low allelic frequency should not be discarded.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with smaller numbers of children have reported the molecular diagnostic yield of genetic testing in pediatric neurodevelopmental diseases to be around 30% -40%, which is higher than what we observed, and may reflect differences in inclusion criteria, which were relatively broad in NYCKidSeq. [33][34][35] We compared the diagnostic yield and concordance of GS and TGP in 642 probands who had both types of tests and found that less than 40% (45 of 113) of diagnoses were achieved by both test modalities. GS-only diagnoses included structural variants and non-exonic sequence variants; however, the majority of GS-only diagnoses were exonic SNVs, most of which were in genes not present on the TGPs.…”
Section: Discussionmentioning
confidence: 99%